2017
DOI: 10.5603/arm.2017.0054
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Selected Questionnaires in the Assessment of Fatigue, Depression and Health Quality in Post-Sarcoidosis Fatigue Syndrome

Abstract: Introduction: The nature of post-sarcoidosis fatigue syndrome (PSFS) is unknown and tools for the assessment of health quality (HQ) in these patients have not been fully assessed. The aim was to validate the Polish version of sarcoidosis health questionnaire (SHQ) and verify the association of HQ with fatigue and depressive symptoms among Polish patients with PSFS. Material and methods: 71 patients with sarcoidosis (34 women, the mean age 47) were divided to: PSFS (n = 21), active sarcoidosis (S-A, n = 27) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Our findings of psychological symptoms being associated with worse HRQoL confirms previous studies that have found a correlation between HRQoL and depressive symptoms in sarcoidosis18 19 and an association between symptom severity and anxiety 11. However, our study included covariates such as organ involvement and comorbidities which have not been included in previous studies.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings of psychological symptoms being associated with worse HRQoL confirms previous studies that have found a correlation between HRQoL and depressive symptoms in sarcoidosis18 19 and an association between symptom severity and anxiety 11. However, our study included covariates such as organ involvement and comorbidities which have not been included in previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…In other chronic pulmonary illnesses, psychological symptoms are associated with lower health-related quality of life (HRQoL) independent of disease severity 15–17. Depressive symptoms have been correlated with lower HRQoL in patients with sarcoidosis; however, these studies have not evaluated the association while controlling for other factors such as disease severity 10 18 19. The previous studies have included those with sarcoidosis requiring medication and those with asymptomatic sarcoidosis or sarcoidosis not requiring medication 10 18 19.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Physical Chalder Fatigue Scale Mental Autoimmune Rheumatic Disease ( Ali et al., 2017 ; Huang et al., 2017 ) Cronbach's α ​= ​0.863 ( Huang et al., 2017 ). Physical Chronic Fatigue Syndrome ( Slomko et al., 2020 ) Fatigue Assessment Scale (FAS) Physical Post-Sarcoidosis Fatigue Syndrome ( Gorski et al., 2017 ) FAS total score correlated significantly and positively with age, Beck Depression Inventory (BDI) score (r ​= ​0.726) and Patient Health Questionnaire-9 (PHQ-9) score (r ​= ​0.788). FAS Physical Fatigue scale score correlated with BDI score (r ​= ​0.670) and PHQ-9 (r ​= ​0.768), while FAS Mental Fatigue scale score was positively associated with age and both BDI (r ​= ​0.702) and PHQ-9 (r ​= ​0.705) scores ( Gorski et al., 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Exercise fatigue is the physiological decline in working ability, activity ability, and range of activity after a strenuous exercise (Narkhede et al, 2016;Górski et al, 2017). The recovery time of exercise fatigue is relatively long and this has an impact on human life and work.…”
Section: Discussionmentioning
confidence: 99%